Family action plan. Family and school necessarily conected. (Journal of Parents and Teachers, 2013)
The author defends that both family and education look for the young people education from different perspectives and with different rolls so it is necessary a relationship between both paying attention to the families diversity. He proposes a family action plan with concrete objectives that systematize and qualify the meetings between family and school without forgetting the formation of both. Finally. The author shows the basic elements that the family action plan must include.
Keywords: Plan; family; collaboration; diversity